EFL Teenagers’ Social Identity Representation in a Virtual Learning Community on Facebook - Laura Verónica Jiménez Guamán (Profile Issues in Teachers' Professional Development, 2012)
In this article I report the findings of a descriptive and interpretative qualitative study carried out in a public school in Bogotá, Colombia. The study aimed at analyzing, describing and exploring teenage students’ social identity representation as observed in their participation in a learning community on Facebook. Data were collected from eight active participants through artifacts and semi-structured interviews in the Dragster Virtual Community on Facebook. Data analysis illustrated that teenagers’ ways of expressing themselves are manifested in conversations and posts and these interactions portray and reflect their social identity inside the group. Their social representations are evaluated, accepted, or denied by the other members in the asynchronous group.